Relevansi Filsafat Pendidikan Islam dengan Tantangan Globalisasi dalam Pembentukan Karakter Muslim - Syuhadatul Husna; Nurul Hikmah; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Islamic Education Philosophy has been a solid foundation in shaping Muslim character for centuries. However, in the dynamic and challenging era of globalization, the relevance of this philosophy is increasingly questionable. This study aims to analyze the extent to which the principles of Islamic Education Philosophy are still relevant in shaping Muslim character that is able to face the complexities of the modern world. Through literature review and comparative analysis, this study reveals that the core values of Islamic Education Philosophy such as monotheism, akhlakul karimah, and knowledge are still very relevant in shaping Muslim character that is faithful, has noble character, and has global competence. This study also identifies specific challenges faced by Islamic education in the era of globalization, as well as strategies that can be applied to overcome these challenges. The results of this study are expected to contribute to the development of a more relevant and effective Islamic education curriculum in shaping a quality Muslim generation.